(3RGjO hGdCef Gdbhej dOhdI GdGeGQGJ GdYQHjI GdeJMOI (B/s - (3GdeYdG(B, (3eGLO YHOGddgs ((3CHhXHj (B- (3OhdI GdGeGQGJ GdYQHjI GdeJMOI (B:s (3eQcR GdGeGQGJ ddOQGSGJ hGdHMhK GdGSJQGJjLjI(B,s, 2022)
(3YbH GdGfSMGH GdHQjWGfj XgQ aQGZ SjGSj hYScQj aj efWbI GdNdjL GdYQHj jgOO HbGA EeGQGJ GdSGMd GdeJUGdM; hdcf GSJWGY GdeZahQ dg, HEPf Gddg JYGdi, GdTjN RGjO Hf SdWGf Bd fgjGf, WjH Gddg KQGg, JTcjd OhdI GJMGOjI aQVJ GMJQGegG hecGfgG aj GdYGde, hJfbSe eNGWQ GdCef Gdbhej dOhdI GdEeGQGJ; GSJfGOkG Edi aQVjI eGQj HhRGf Mhd WHjYI GdOhdI, Edi KdGKI CfeGW(B: (3GdJgOjOGJ GdJj JSJgOa acQI GdOhdI, hGdJgOjOGJ GdJj JhGLg eDSSGJ GdOhdI, Ke GdJgOjOGJ GdeJhbYI ddbGYOI GdeGOjI ddOhdI, hbO OYe GdTjN RGjO GdacQI GdJj bGeJ YdjgG GdOhdI, hCfTC GdeDSSGJ GdeYfjI HMeGjI bGYOJgG GdeGOjI; eG LYd GdGJMGO, GdPj JMbb jhe (B2 (3OjSeHQ (B1971(3, VeGkfG ddGSJbQGQ GdCefj hGdQaGgjI aj gPG GdLRA ef GdhWf GdYQHj(B.s
Keywords: (3RGjO Hf SdWGf Bd fgjGf, (B1918-2004s; (3GdCef Gdbhej (B-- (3GdEeGQGJ GdYQHjI GdeJMOIs; (3GdEeGQGJ GdYQHjI GdeJMOI (B-- (3JGQjNs; (3GdEeGQGJ GdYQHjI GdeJMOI (B-- (3GdCMhGd GdGbJUGOjIs; (3GdEeGQGJ GdYQHjI GdeJMOI (B-- (3GdCMhGd GdSjGSjIs; (3GdEeGQGJ GdYQHjI GdeJMOI (B-- (3GdCMhGd GdGLJeGYjIs